ANALISIS HARGA SAHAM, LIKUIDITAS SAHAM, EARNING PER SHARE, DAN PRICE EARNINGS RATIO ANTARA SEBELUM DAN SETELAH STOCK SPLIT - Mazra Iffah Labibah; Susi Dwimulyani (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2014)
The purpose of this study analysis the influence of stock price, stock liquidity, EPS growth, and price earnings ratio on the stock split. This research also analysis whether there are any difference in stock price, stock liquidity, EPS growth, and price earnings ratio before and after the company decided to executed a stock split.The samples of this research are companies that listed in Indonesia Stock Exchange (IDX) in the 20082013 period and conduct a stock split. Based on samples criteria which have been determined, there are 89 companies which qualified to be used as samples. This research used Wilcoxon Signed Rank Test and Logistic Regression for hypothesis testing. The results of this research show that there are no significant differences in stock price, stock liquidity, EPS growth, and price earnings ratiobetween before and after stock split. This study also indicates that stock price and stock liquidity have significant influence towards stock split decision while EPS growth and price earnings ratio don’t have any significant influence towards stock split decision.